PET imaging-guided chemogenetic silencing reveals a critical role of primate rostromedial caudate in reward evaluation - Yuji Nagai (Nature Portfolio, 2016)
Processing the value of reward is thought to involve the rostromedial caudate (rmCD), but a causal demonstration is lacking in primates. Here the authors use chemogenetics and PET imaging to show that inactivation of rmCD leads to impairments in reward value judgments.